EvaluateEvaluate the polynomial when x=3, y= -2 and z=-5 x to the second power + y to the second power - xy

4 Answers | Add Yours

sciencesolve's profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

The polynomial you have given has not the variable z, therefore you've omitted it.

The polynomial in discussion is x^2+y^2-xy.

The value of the polynomial for x=3 and y=-2.

x^2+y^2-xy = 3^2 + (-2)^2 - 3*(-2) =>

=> x^2+y^2-xy = 9 + 4 + 6 = 19

The value of polynomial is 19.

litteacher8's profile pic

litteacher8 | High School Teacher | (Level 3) Distinguished Educator

Posted on

Is there a z missing? X squared is 3 squared, which equals 9. Squared means multiply the number by itself. Y squared is -2 squared, which is 4. Two negative numbers multiplied together make a positive, and 2 times 2 is 4. X times y is 3 times -2, which is - 6. Now you have 9 + 4 - (-6). When you subtract a negative number, you add. So it becomes 9 + 4 + 6 = 19.
cookiee-monster's profile pic

cookiee-monster | Student, Grade 11 | (Level 1) Honors

Posted on

x²+y²-xy

= (3)²+(-2)²-(3)(-2)

= 9+4-(-6)

= 9+4+6

= 19

note:

  • Be sure to follow BEDMAS(bracket, exponent, division, multiplication, addition, and subtraction) if division and multiplication appears, do it from left to right. same with addition and subtraction
  • When substituting, be sure to bracket them no matter what
  • When there's no equation sign, bracket=multiply. Example xy=(3)(-2) = 3 x -2 = -6
istulin's profile pic

istulin | Student, College Freshman | eNotes Newbie

Posted on

x² + y² - xy

subsitute the values given x=3 ; y=-2

(3)² + (-2)² - (3)(-2)

simplify

9 + 4 - (-6)

9 + 4 + 6 (why did it become +? because - times - is positive)

= 19

We’ve answered 318,915 questions. We can answer yours, too.

Ask a question